Affect Labeling as an Intentionally Regulatory Mechanism for Emotion Management - Zanyar Nathir Ghafar (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
The phenomenon of transmitting feelings via language methods also referred to as "impact labeling," has the potential to lessen the intensity of our negative emotional experiences. In contrast to explicit procedures used to regulate emotions, the process of effect identification may not be seen as an intentional regulating mechanism when it first occurs. This was made by comparing the effects of affect tagging to the outcomes of deliberate emotion management. This study aims to construct a comparison analysis with reappraisal, a kind of explicit emotion management, and offer a complete review of the existing literature on affect classification. Additionally, to provide a comprehensive assessment of the current research on affect category. The investigation will be carried out with a significant focus on four areas of effects: the experiential, the autonomic, the neurological, and the behavioral domains. The second sources such as documents, and review previous published papers have been used as a methodology Findings The research findings indicate that affect category has resulted in various outcomes, including reduced self-reported effect, decreased autonomic activity, and activation of similar neural regions, in addition to addressing other issues detailed throughout this review paper.